General mass treatment for Z boson production in association with a heavy quark at hadron colliders - Guzzi M.; Nadolsky P.; Reina L.; Wackeroth D.; Xie K. (EPJ Web of Conferences, 2024)
We present the application of the ACOT and S-ACOT general mass variable flavor number schemes to proton-proton collisions with particular attention to the production of final states with at least one heavy quark. Subtraction and residual heavy-quark parton distribution functions are introduced to facilitate the implementation of this scheme at higher orders in perturbative QCD. The calculation of Z-boson hadronic production with at least one b jet beyond the lowest order in QCD is considered for illustration purposes.